Pengaruh Komunikasi dan Iklim Kerja Terhadap Motivasi dan Kinerja Pegawai pada Dinas Tanaman Pangan Holtikultura dan Perkebunan Provinsi Riau - Charina Dwiki Asputri; Suarman Suarman; Yulia Efni (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2019)
This study aims to examine and analyze the communication spak and the work climate performance in which motivation is regarded as an intervening variable. The study was conducted at the Horticultural Food and Plantation Office of Riait Province.The data consist of primary data and secondary data. The population of this research are as big as 153 people. The needed data were collected by using a questionnaire addressed to 111 employees of the Hottikultura Food and Agriculture Service Office in Riau Province. The Slovin formula is used to carried the quistionare. Descriptive analysis method is used to describe the characteristics of respondents and research hypotheses by using relevant statistical tests. The variables of communication and work climate are as independent variables, while performance is as the dependent variable, and the motivation is regarded as intervening or mediating variable. The path analysis is used to analyze the collected data.The results of the study indicate that communication directly influences significantly to motivation. Work climate has a direct significant effect on motivation the communication has a significant direct effect on performance. Whole work climate contributes positively to performance. The motivation correlates significantly on performance. Indirectly, motivation has an intensive mediating role in communication and the communication is over performance. The motivation has a positive median role on the influence of the work climate on performance. Increasing the effectiveness of communication and work climate are recommended to optimize employee performance and motivation.